Digital Media Use: Differences and Inequalities in Relation to Class and Age. (November 2015) - Yates, Simeon; Kirby, John; Lockley, Eleanor
This paper takes a national perspective on issues of digital media use. The paper draws upon the OfCom Media Literacy 2013 survey to explore how digital media use varies in regard to two major social variables – class and age. Both class and age feature predominantly in UK policy on digital access and use. Class and age are invoked as either things that create barriers to access or as issues to be addressed and managed through using digital media. Despite the large body of work on the 'digital divide' there is a more limited literature that explicitly addresses class. The paper seeks to act as an empirical reference point for the development of further debate around the links between class and digital media use. The paper presents a factor analysis of the OfCom data that identifies five main areas of digital media use. These five factors are then subjected to a multiple analysis of variance to explore the effects across, between and within age and class categories. A cluster analysis based on the factors identifies seven main 'User Types' that are again compared across class and age. The paper finds that class and age act relatively independently as predicators of digital media use and neither compound nor mitigate each other's effects. Importantly the paper notes that the greatest levels and breadth of Internet use can be found in NRS social class groups AB and to an extent C1. In contrast the greatest levels of non-use and limited use can be found in NRS social class groups DE. In conclusion the paper notes that age still acts as the major explanatory variable for overall use and some specific types of use, but that class also independently acts to explain patterns of digital media use. As a result any simplistic policy expectations that digital access and use issues will become less relevant as age demographics change have to be questioned.